The impact of ESG strategies on growth in the logistics industry - Sadowski, Adam; Gniadkowska-Szymańska, Agata; Sokolovskij, Edgar; Jędrzejczak, Ryszard (Transport, 2024)
The aim of the article is to analyse the relationship between company growth, measured as an increase in Earnings Per Share (EPS) in 3- and 5-year periods, and companies’ financial condition, measured using the Altman z-Score (AS) model. The study was carried out on the example of companies included in the WIG Index and Warsaw Stock Exchange Index (in Polish: Warszawski Indeks Giełdowy – WIG) Environmental, Social, and Governance (ESG) between 2013 and 2020. Furthermore, among the companies included in the WIG index, companies belonging to the logistics industry were distinguished. An analysis of linear and panel relationships was used to verify the nature of the relationships between the variables taken into account. The z-Altman index was found to have a positive effect on company growth in a 3-year period for companies from the transport and logistics industry and all companies included in the WIG ESG index. Regarding company growth over the longer 5-year period, the influence of the z-Altman index on growth was not observed. Therefore, the results for companies in the WIG index show that for company growth in both the 3- and 5-year periods, the financial and economic condition of a company, measured by the z-Altman index, has no impact on the size of this growth, which was also confirmed by panel models.